2007
DOI: 10.1007/s00198-007-0476-z
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of vitamin D deficiency among adolescents with anorexia nervosa

Abstract: Summary-Fifty adolescents with AN and 200 healthy girls underwent vitamin D screening. Girls with AN reported exceptional compliance with vitamin D supplementation and PTH concentrations were lower. Vitamin D deficiency was less common in the group with AN, but when race was considered, the trend was no longer significant.Introduction-The objective of this study was to determine whether patients with anorexia nervosa (AN) are more compliant with supplementation and have a lower prevalence of vitamin D deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 22 publications
5
46
1
6
Order By: Relevance
“…Patients with AN have been shown previously to have a better vitamin D status compared to healthy control subjects. 28 The benefit is related in part to more consistent compliance with vitamin D supplementation and potentially, to increased levels of bioavailable vitamin D in underweight patients. The positive effects of vitamin D on the oral health of the current patients with AN, in addition to not having the deleterious effects of the binging/purging behavior, may have improved the overall oral health of this current clinic-based sample.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AN have been shown previously to have a better vitamin D status compared to healthy control subjects. 28 The benefit is related in part to more consistent compliance with vitamin D supplementation and potentially, to increased levels of bioavailable vitamin D in underweight patients. The positive effects of vitamin D on the oral health of the current patients with AN, in addition to not having the deleterious effects of the binging/purging behavior, may have improved the overall oral health of this current clinic-based sample.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, only 2 of the 63 (3 %) Japanese patients studied were taking a multivitamin supplement containing vitamin D2 [1]. In our study, 85 % of patients reported taking vitamin D supplements [2]. In addition, our patients' mean body mass index (BMI) was 18±1.6 kg/m 2 , whereas their sample included a much lower mean BMI of 14.6±2.5 kg/m 2 .…”
mentioning
confidence: 75%
“…Thus, the degree of malnutrition was significantly worse among their study subjects than ours. Our patients reported drinking 1.7 glasses of vitamin D-supplemented milk daily [2]. Dr. Hotta's letter did not specify milk consumption in the Japanese cohort.…”
mentioning
confidence: 99%
“…In the United States, more girls with AN receive vitamin D supplementation than healthy controls, and the prevalence of vitamin D deficiency is thus lower among adolescents with AN than in healthy subjects in that country (19). However, in Japan, the general population, as well as patients with AN, exhibits a high prevalence of vitamin D insufficiency.…”
Section: Discussionmentioning
confidence: 97%